PC.100 Meeting the Demands of the Neonatal Workforce – Developing an Advanced Neonatal Nurse Practitioner Course. (9th June 2014) - Philpott, A; Inman, C
Abstract : Background: Reductions in the number of junior doctors and limitation on working hours prompted units in the West Midlands (WM) to look for alternative workforce solutions to populate neonatal rotas and provide neonatal care. A small number of Advanced Neonatal Nurse Practitioners (ANNPs) were already working in the region. A local higher education provider offered a programme in Advanced Practice and a double neonatal Advanced Health Assessment for neonates was developed, awarding a MSc in Advance Practice (Nursing). Aims: To record the number of ANNPs trained within the West Midlands since the introduction of the programme. To describe changes in the MSc programme in response to local demand. Results Numbers: There have been 4 cohorts of students since the course started. Cohort 1–6 students – 5 MSc (and one Pg Diploma award) Cohort 2–7 students – 5 MSc (two Pg Diploma awards one moved from the area) Cohort 3–3 students – 2 MSc (one MSc in progress) Cohort 4–15 students – ongoing Changes: Cohort 1 consisted of a single neonatal module; Cohort 2 progressed to a double neonatal module with a non-medical prescribing qualification. For Cohort 3 the syllabus was revised to map to the RCPCH training programme. All cohorts involved teaching and assessment in practice for neonates with teaching provided by clinicians. Cohort 4 further emphasised differential diagnosis with OSCE in University and in neonatal units as well as using case based learning and simulation activities. Conclusions: The course is successfully training and educating an increasing number of ANNPs. Local clinicians shape the education of their student ANNPs and delivery in the WM allows study close to home. Limitations: Student numbers have been relatively small. Some who have had limited previous opportunity for academic development lack a first degree, are confronted with a steep learning curve and require substantial support. This is the first large cohort and it will be important to follow this group and obtain information about their progress.